2018
DOI: 10.1002/brb3.1089
|View full text |Cite
|
Sign up to set email alerts
|

Spatial learning and long‐term memory impairments in RasGrf1 KO, Pttg1 KO, and double KO mice

Abstract: BackgroundRasGrf1 is a guanine‐nucleotide releasing factor that enhances Ras activity. Human PTTG1 is an oncoprotein found in pituitary tumors and later identified as securin, a protein isolated from yeast with a reported role in chromosome separation. It has been suggested that RasGrf1 is an important upstream component of signal transduction pathways regulating Pttg1 expression and controlling beta cell development and their physiological response. At memory formation level, there are contradictory data rega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Functional analysis has demonstrated that this protein stimulates the dissociation of GDP from RAS protein. The Ras-GEF signaling pathway may be important for long-term memory [39]. A recent study in a mouse model of depression suggests that altering this gene's expression may be an essential link in the mood-regulating effects of drugs [40].…”
Section: Discussionmentioning
confidence: 99%
“…Functional analysis has demonstrated that this protein stimulates the dissociation of GDP from RAS protein. The Ras-GEF signaling pathway may be important for long-term memory [39]. A recent study in a mouse model of depression suggests that altering this gene's expression may be an essential link in the mood-regulating effects of drugs [40].…”
Section: Discussionmentioning
confidence: 99%
“…Ccne1, ccne1 and ccnb1 belonged to the cyclin family, and were essential for the control of the cell cycle (Sauer et al, 1995). The other genes, such as ppp1cb and pttg1, played vital roles in chromosome stability (Barker et al, 1994;Manyes et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…A further fourteen genes ( 1700048O20Rik , Abdh1 , Adat2 , Gvin1 , Irgm2 , Itgb3bp , Kbtbd11 , Lacc1 , Nmrk1 , Pyurf , Slc25a37 , Slc39a2 , Stxbp2 , Zfp125 ) were commonly regulated between hippocampus and cerebellum but were not hypothalamic cPRGs. The cPRG transcripts most dramatically down-regulated (2-fold or more) are Pttg1 , a transcriptional activator associated with development [22]; Mid1 , implicated in structural brain defects, Huntington’s and Alzheimer’s pathology [23], 4833420G17Rik , a predicted protein (orf) of unknown function, and Pisd-ps3 , phosphatidylserine decarboxylase pseudogene 3, regulated in aging [24]. Mrpl20 and Xaf1 are genes encoding known proteins of unknown function in the nervous system.…”
Section: Resultsmentioning
confidence: 99%